Analysis of the Dilemma of Overseas Cross-cultural Communication of Chinese Animation Movies and the Strategy of Cross-cultural Communication in the New Media Environment: “Nezha: Birth of Demon” as An Example: 中国动画电影海外跨文化传播困境与新媒体环境下跨文化传播策略探析 ——以《哪吒之魔童降世》为例 - WANG , Yue (Published by Confucius Institute UNS, 2022)
In the 21st century, modern media technology allows cultural products to circulate throughout the world. Movies have become an important carrier of cultural exchange and dissemination. Animated movies become a breakthrough in the cross-cultural dissemination of Chinese culture. This article takes the Chinese animation movie